Letting Down the Team? Social Effects of Team Incentives - Reproduction Report of Babcock et al. (2015) - Daniel Pelloth; Patrick Hoffmann (Institute for Replication (I4R), 2024)
The experimental study "Letting Down the Team? Social Effects of Team Incentives" by Philip Babcock and colleagues (2015) proposes that team incentives significantly enhance individual performance through social pressure and peer effects. The findings suggest that individuals are motivated by a desire to avoid disappointing their teammates, indicating that social dynamics, such as guilt and social pressure, play a crucial role in shaping behavior in team settings. In this report, we computationally reproduce the results from the original paper and perform several robustness checks. Overall, we ascertain the good reproducibility of the study and find that the results hold across the performed robustness checks.
Keywords: 330